Особенности показателей эхокардиографии у больных ревматоидным артритом - Алексеева, А.А. (Таврический медико-биологический вестник, 2010)
Метою нашого дослідження було вивчити структурно-функціональні показники міокарда серця у 129 хворих на ревматоїдний артрит (РА).За результатами ЕхоКГ, більшість пацієнтів з РА (64,38%) мають гіпертрофію лівого шлуночку (ЛШ), що передбачає найбільш високий серцево-судинний ризик, включаючи летальні. Виявлено різні типи ремоделювання ЛШ з переважанням ексцентричного варіанту гіпертрофії ЛШ. Для хворих на РА також характерно порушення всіх фаз діастоли, включаючи як процеси активної релаксації, так і зміни показників жорсткості камери ЛШ. The aim of our study was to examine the structural and functional indices of the myocardium of the heart in 129 patients with rheumatoid arthritis (RA). As a result of echocardiography, the majority of patients with RA (64.38%) have left ventricular hypertrophy, providing the highest cardiovascular risk, including lethal. Identified different types of LV remodeling with a predominance of eccentric version of left ventricular hypertrophy. For patients with RA is also characterized by a violation of all phases of diastole, including both the processes of active relaxation and changes in indicators of left ventricular chamber stiffness.